THE ROLE OF REGIONAL PARTIES IN INDIAN POLITICS-A STUDY - Vanaja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In a democracy, political parties provide an agency to the society to gather different views on various issues and to present these to the government. They bring various representatives together so that a responsible government could be formed. They provide a mechanism to support or restrain the government, make policies, justify or oppose them. India has a multi-party system. The multi-party system in India has many political consequences. In the event of an election, the norm states that the party with the majority votes wins the election. However, in order to form a government, a party should have a certain number of votes. This need not happen, leading to problems. The majority party has to therefore join hands with a regional party in order to form government. This is where the importance of the smaller regional parties comes into play.